The Origin and Diversification of the Hyperdiverse Flora in the Chocó Biogeographic Region - Pérez-Escobar, Oscar Alejandro; Lucas, Eve; Jaramillo, Carlos; Monro, Alexandre; Morris, Sarah K.; Bogarín, Diego; Greer, Deborah; Dodsworth, Steven; Aguilar-Cano, José; Sanchez Meseguer, Andrea; Antonelli, Alexandre (Frontiers in Plant Science, 2019)
Extremely high levels of plant diversity in the American tropics are derived from multiple interactions between biotic and abiotic factors. Previous studies have focused on macro-evolutionary dynamics of the Tropical Andes, Amazonia, and Brazil’s Cerrado and Atlantic forests during the last decade. Yet, other equally important Neotropical biodiversity hotspots have been severely neglected. This is particularly true for the Chocó region on the north-western coast of South and Central America. This geologically complex region is Earth’s ninth most biodiverse hotspot, hosting approximately 3% of all known plant species. Here, we test Gentry’s [1982a,b] hypothesis of a northern Andean-Central American Pleistocene origin of the Chocoan flora using phylogenetic reconstructions of representative plant lineages in the American tropics. We show that plant diversity in the Chocó is derived mostly from Andean immigrants. Contributions from more distant biogeographical areas also exist but are fewer. We also identify a strong floristic connection between the Chocó and Central America, revealed by multiple migrations into the Chocó during the last 5 Ma. The dated phylogenetic reconstructions suggest a Plio-Pleistocene onset of the extant Chocó flora. Taken together, these results support to a limited extend Gentry’s hypothesis of a Pleistocene origin and of a compound assembly of the Chocoan biodiversity hotspot. Strong Central American–Chocoan floristic affinity may be partly explained by the accretion of a land mass derived from the Caribbean plate to north-western South America. Additional densely sampled phylogenies of Chocoan lineages also well represented across the Neotropics could enlighten the role of land mass movements through time in the assembly of floras in Neotropical biodiversity hotspots.